Partenogenesis? Tinjauan Teologis dan Sains Tentang Kelahiran Yesus dari Seorang Perawan Maria - Erastus Sabdono; Stephanie Rombot; Felix Christian; Donny Stevianus Nunung; Stephanie Erastus (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
This research aims to conduct an in-depth study of claims about the birth of Jesus from a virgin, which is thought to have occurred through the process of parthenogenesis. In Christian tradition, the birth of Jesus from Mary is considered a miracle involving the concept of birth without human fertilization. By using descriptive qualitative methods through an interdisciplinary approach that includes hermeneutics (text analysis and science), this research tries to reveal whether parthenogenesis is a scientific possibility that can explain the birth of Jesus. This research method involves textual analysis of the birth narrative of Jesus in the New Testament, as well as scientific examination of the possible process of parthenogenesis in human reproduction. The results of the theological and scientific analysis will be evaluated to determine to what extent the claim of Jesus' virgin birth is acceptable from the perspective of faith and science. The results of this research show that the event of Jesus' birth can be called parthenogenesis if the reader looks at it through a scientific lens. On the other hand, the event of Jesus' birth is the intervention of God and His Holy Spirit as an absolute thing that cannot be separated and denied and even replaced with other concepts.